History Repeats: Large Scale Synchronous Biological Turnover in Avifauna From the Plio-Pleistocene and Late Holocene of New Zealand - Rawlence, Nicolas J.; Scofield, R. Paul; McGlone, Matt S.; Knapp, Michael (Frontiers in Ecology and Evolution, 2019)
New Zealand’s unique biodiversity has long been considered both the product of a ‘Moa’s Ark’ isolationist experiment since the break-up of Gondwana and the result of millions of years of transoceanic migration. Increasingly, palaeontological and genetic evidence suggest that much of New Zealand avifauna results from dispersal from Australia. We synthesise a growing number of evolutionary genetic studies to show a previously unrecognised clustering of divergence times in Australian and New Zealand bird species pairs, across the avian phylogeny, around 2.5 million years ago at the beginning of the Pleistocene. The timing coincides with the dramatic environmental changes associated with the Plio-Pleistocene transition. Intriguingly, recent anthropogenic impacts and environmental modifications are replicating in some important ways conditions during the Pleistocene glacial periods, resulting in a new wave of avian ‘native invaders’ into New Zealand.